Resveratrol supplementation reduces oxidative stress and modulates the immune response in free‐living animals during a viral infection. (28th August 2018) - Sebastiano, Manrico; Eens, Marcel; Messina, Simone; AbdElgawad, Hamada; Pineau, Kévin; Beemster, Gerrit T. S.; Chastel, Olivier; Costantini, David
Abstract: Diet quality may have an important effect on the regulation of oxidative status and the immune system during an infectious disease. However, the relationship among intake of specific dietary molecules, an individual's oxidative status and the occurrence and progress of a viral disease remains almost unexplored in free‐living organisms. Here, we study a wild, long‐lived animal, the Magnificent frigatebird Fregata magnificens to investigate: (a) the differences in a number of physiological traits (biomarkers of blood oxidative status, corticosterone (CORT), immunity and inflammation) between sick and healthy nestlings; and (b) whether experimentally increased intake of resveratrol (a polyphenol with antioxidant and antiviral properties) affects these physiological markers during the progress of a severe viral disease. Birds with visible clinical signs showed higher oxidative damage, haemolysis and haemagglutination scores and lower antioxidant defences in comparison with birds without clinical signs. At the end of the experiment, supplemented birds showed the following: (a) increased plasma haptoglobin levels and circulating antioxidant defences; (b) reduced generation of lipid oxidative damage; and (c) negligible to no influence on immune markers, baseline CORT levels and activity of antioxidant enzymes. Our work illustrates how the availability of specific organic molecules in the diet may constrain the individuals' capacity to cope with viral infections in free‐living animals. plain language summary is available for this article. Abstract : Plain Language Summary